Addressing the needs of the children's integrated workforce: A method for developing collaborative practice through joint learning. (29th November 2016) - Harrington-Vail, Amanda; Simpson, Jennifer; Haider, Sharif; Bardsley, Janet; Brown, Gill; Bayley, Kenneth; Dale-Emberton, Ann
Abstract : The delivery of welfare, health and educational provision to the majority of children aged 0–18 in England is primarily led by local authorities via their children's integrated service. In 2004 the children's integrated service model was launched and it promised the benefits of an integrated and collaborative system of working, regarding flexibility and responsiveness to national policy, local development and capacity building (Robinson et al, 2008). However, the implementation and emergence of this model has been characterised by competing local and national agendas, practitioner misunderstanding and lack of trust, a lack of strong leadership and also financial restrictions. It can therefore be contended that conceptually children's integrated services are not operating fully with a collaborative and integrated workforce. As a possible solution to the current situation, it is proposed that joint learning, along with a combined continual professional development (CPD) framework, be made available as a valuable starting point for such organisations. Learning and working together has benefits for children and practitioners, and especially, as this article will argue, for playwork practitioners.